Características morfológicas dos músculos e qualitativas da carne de cordeiros suplementados e terminados em diferentes índices de área foliar residual - Silva, Camila Lacerda [UNESP] (2013)
Aiming at the morphological study of qualitative muscles of the meat and the correlation of the evaluated parameters Gluteus medius, Longissimus and Triceps brachii animals finished in different leaf area index (LAI) ( 0,8;1,4; 2,0 and 2,6%) of pasture comprising TIFTON 85 (Cynodon spp.) being supplemented or not with energy protein concentrate (0,7% of body weight), we used 48 lambs SPRD, uncastrated, with an average weight of 33,7 lbs . The animals were confined for the duration of the night in individual stalls, where they supplement with 18% crude protein. Reached 32 kg body weight, the animals were slaughtered and samples of the Gluteus medius, Longissimus and Triceps brachii were collected for evaluation of morphological parameters: frequency, area, and total area relative. Hit the post mortem (24 hours after slaughter) and rigor mortis, samples were collected from portions of the Gluteus medius, Longissimus and Triceps brachii and to evaluate the quality characteristics: pH, color, weight loss by cooking and smoothness (shear force). There were no interactions (P>0,05) between the LAI and the levels of supplementation for the pH values of the muscles. In the study of the Gluteus medius, keep animals in higher LAI and without supplementation may be a good alternative to the achievement of desirable parameters by consumers of sheep meat. In assessing Triceps brachii muscle, animals kept in IAF 1,4 and without supplementation have higher meat lightness L* and lower yellowness b*. There was a significant negative correlation (P<0,05) between the SO and FOG, FOG and FG fibers and characterizing the process of modulation, and FOG fiber reflecting the proportionality of frequency of SO and FG muscle fibers of the muscles Longissimus and Gluteus medius...